A case study on customers' satisfaction towards maybank2u.com Maybank Al-Idrus Commercial Centre Kuching Branch / Ratnawate Panie - Panie, Ratnawate (2002)
"Customer satisfaction is the profound measure of quality." The purpose of this research is to examines customers' satisfaction towards the Internet banking; maybank2u.com. Specifically, it addresses issues such as customers' awareness, customers' loyalty and factors that affect the adoption of maybank2u.com. It then discusses level of customer satisfaction towards pre sales service, product delivery and service delivery and presentation that remarks the customers' overall satisfaction. This study shows that Internet banking allows customers to conduct certain transaction online at anytime and thus it reduces the number of physical visit to a bank. This added convenience to the customers thus contributes customer loyalty toward the product.